Web service invocation framework adding wheels to web services. - Chaudhari, Anshuk Pal
The open source initiatives have transformed the technical landscape by leaps and bounds in the past two decades. It has gone a long way toward breaking the stranglehod of monopolistic software companies over technologies. When programmers have the ability to read, redistribute and modifty the source code for a piece of software, the software evolves faster and better. It happens at a speed that is way faster compared to the slow pace of conventional software development.